Policy as an object of reflection (2011)
The reﬂection on the politics is a matter of difﬁcult description.Maybe, the above-mentioned, is due to the same concept,when not to the variable character of a term that has been fromdifferent disciplines. Also because the politics, like reﬂectionobject, is presented, in spite of its daily use, as a controversialterm and of different use and understanding, according to theenvironment and the moment in that it is used. On the otherhand, the political science, disciplines in charge ofapproachingits reﬂection, it has shared study object with the philosophy,the history of the ideas, the sociology, or the right. The presentwork notices as main objective, to promote the debate and thediscussion about the utility of the political science as academicdiscipline and professional that’s responds or tries to respondqueries like: what’s the meaning of politics? Or When we speakof political science, of what do we speak?